Pre-ovulatory hormones on day of human chorionic gonadotropin trigger and assisted reproductive technique outcomes in different ovarian response groups - Subarna Mitra; Madhuri Patil; Milind Patil; Prasanta Kumar Nayak (Wolters Kluwer Medknow Publications, 2021)
Background: Evidence regarding impact of pre-ovulatory hormone levels on assisted reproductive technique (ART) outcomes in different ovarian response groups is sparse. Aims: The objective of this study was to evaluate and compare the association between pre-ovulatory hormonal profile and ART outcomes in different ovarian responses. Setting and Design: This is a single-centre retrospective cohort study of 273 non-donor fresh ART cycles between January 2013 and June 2016. Materials and Methods: Data on clinical profile, basal and peak hormonal levels, characteristics of controlled ovarian stimulation and ART outcomes were collected. Progesterone elevation (PE) was defined as pre-ovulatory serum progesterone >1.5 ng/mL or progesterone to oestradiol ratio >1. The association between peak hormonal levels and ART outcomes in poor (≤4 oocytes retrieved), intermediate (5-13 oocytes retrieved) and high (≥14 oocytes retrieved) ovarian responders was analysed and compared. Statistical Analysis: Continuous and categorical variables were summarised as median (interquartile range) and percentages, respectively, and compared using Kruskal-Wallis H-test or Mann-Whitney U-test and Chi-square test or Fisher's exact test, respectively. Results: The incidence of PE, by both criteria and clinical pregnancy rates (35.7%, 36.8% and 18.6% in high, normal and poor responders, respectively; P = 0.073), was similar among the three response groups. Except fertilisation rates in normo-responders, PE did not influence ART outcomes in any response group. Furthermore, there were no differences between peak hormone concentrations or incidence of PE between those who conceived and those who did not. Conclusion: Pre-ovulatory sex steroid levels do not seem to be the primary determinant of ART outcomes in any ovarian response category; hence, decision to freeze all embryos in the event of PE should be tailored.